Peculiarities of Physical Training in the Case of Ashihara Karate Style Practitioners - D. Mocioaca; M. Dragomir (Editura Universitatii Transilvania din Brasov, 2023)
Sports training must obey well-defined principles and rules to lead to progress in the training of practitioners. The purpose of the research is to discover those innovative methods and techniques in martial arts training that lead to the development of physical parameters as well as technical-tactical training. The experimental research took place over a period of 6 weeks, including 12 athletes, and members of the Sen Craiova Sports Club, aged between 20-35 years. Following the analysis of the obtained results, it is evident that the level of general and specific physical training contributes substantially to the increase of the training level of the athletes, an aspect that is reflected in the manifestation of the motor indices, of the change in their physical, functional and technical-tactical parameters.